Maternal perspectives on postnatal breastfeeding support: Integrating perceptions for a mother-friendly ten steps framework - Lojander, Jaana (fi=Turun yliopisto|en=University of Turku|, 2025)
Integrating a maternal perspective into breastfeeding support is important for improving the quality and relevance of the support provided, which may, in turn, enhance breastfeeding outcomes. The aim of this study was to examine mothers' perceptions of postnatal breastfeeding support and factors associated with exclusive breastfeeding. Furthermore, the study investigated the impact of the Baby-Friendly Hospital Initiative (BFHI) on breastfeeding support. The findings were integrated into the Ten Steps framework, thereby incorporating a maternal perspective. The study comprised four sub-studies. A cross-sectional study examined mothers' (n=160) perceptions of breastfeeding support in a non-Baby-Friendly hospital. An integrative literature review synthesized the existing literature on mothers' perceptions of breastfeeding support in Baby-Friendly hospitals. A quasi-experimental study compared mothers' perceptions of breastfeeding support before (n=162) and after (n=163) implementation of BFHI, and a correlational study investigated the continuation of breastfeeding among postpartum mothers (n=80) following discharge from a Baby-Friendly hospital. Breastfeeding support in the immediate and early postnatal period was of great significance, contributing to exclusive breastfeeding. Early skin-to-skin contact and breastfeeding initiation were common practices, but further support did not meet mothers' needs. A family-centered care approach, which fosters parenting self-efficacy, was identified important in the promotion of exclusive breastfeeding. The implementation of BFHI improved breastfeeding support from the maternal perspective. After hospital discharge, mothers preferred more timely face-to-face breastfeeding support from professionals. The results provided evidence for improvements needed in postnatal breastfeeding support to make it more mother-friendly. Implementation of BFHI in accordance with the needs of the mother and a family-centered approach is recommended to ensure evidence-based breastfeeding support and to promote breastfeeding.

Kymmenen askelta kohti äiti- ja vauvamyönteistä imetyksen tukemista: äitinäkökulma synnytyksen jälkeiseen imetystukeen Äitien näkökulman sisällyttäminen imetystukeen on tärkeää, jotta imetystuen laatua ja siten imetyksen toteutumista voidaan parantaa. Tutkimuksen tarkoituksena oli kuvata äitien näkemyksiä ammattilaisten tarjoamasta synnytyksen jälkeisestä imetystuesta ja täysimetykseen yhteydessä olevia tekijöitä. Lisäksi tutkimuksessa kuvattiin Vauvamyönteisyysohjelman vaikutusta imetyksen tukemiseen sairaalassa. Tulokset integroitiin Kymmenen askelta onnistuneeseen imetykseen-käytäntöihin suosituksina äitimyönteisemmän imetystuen toteuttamiseksi. Tutkimus sisälsi neljä osatutkimusta. Poikkileikkaustutkimuksessa kuvattiin äitien (n=160) näkemyksiä imetystuesta ei-vauvamyönteisessä synnytyssairaalassa. Integratiivisessa kirjallisuuskatsauksessa koottiin yhteen aiempi tutkimusnäyttö äitien näkemyksistä imetystuesta vauvamyönteisiksi sertifioiduissa sairaaloissa. Kvasikokeellisessa tutkimuksessa verrattiin äitien näkemyksiä sairaalan imetystuesta ennen (n=162) Vauvamyönteisyysohjelman käyttöönottoa ja sen jälkeen (n=163). Korrelatiivisessa tutkimuksessa selvitettiin vauvamyönteisestä sairaalasta kotiutuneiden äitien (n=80) imetyksen toteutumista. Imetystuella oli keskeinen merkitys täysimetyksen toteutumisessa. Varhainen ihokontakti ja ensi-imetys toteutuivat hyvin, mutta vuodeosastolla toteutunut imetystuki oli riittämätöntä eikä aina vastannut äitien tarpeita. Perhekeskeinen hoito synnytyssairaalassa ja vanhemmuuden minäpystyvyyden vahvistaminen ovat tärkeitä tekijöitä täysimetyksen edistämisessä. Vauvamyönteisyysohjelman käyttöönotto paransi imetystukea sairaalassa. Sairaalasta kotiutumisen jälkeen äidit toivoivat, että kasvotusten toteutettavaa imetystukea olisi ammattilaisten taholta saatavilla nykyistä oikea-aikaisemmin. Tulosten perusteella synnytyksen jälkeistä imetystukea voidaan kehittää äitimyönteisemmäksi. Vauvamyönteisyysohjelman käyttöönotto, joka huomioi äitien yksilölliset tarpeet ja perhekeskeisen toteutuksen, on suositeltavaa näyttöön perustuvan imetystuen varmistamiseksi ja imetyksen edistämiseksi.